Encyclopedia of Ukraine. - Kubiĭovych, Volodymyr, 1900-1985 (University of Toronto Press, 1988)
The appearance of Volume II of the Encyclopedia of Ukraine makes the second stage of a major publishing project. Based on twenty-five years' research by more than 100 scholars from around the world, the encyclopedia provides the most essential information about Ukraine and its people, history, geography, economy, and cultural heritage.